Pengaruh keragaman jamur Metarhizium anisopliae terhadap mortalitas larva hama Oryctes rhinoceros dan Lepidiota stigma - Syafira Athifa; Syaiful Anwar; Budi Adi Kristanto (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
The research was conducted to evaluate the effect of variant of M. anisopliae on mortality of Oryctes rhinoceros and Lepidiota stigma. Variants ofM. anisopliae to be used were Karimun Jawa, Semarang and Magelang (host O. rhinoceros), and UGM (host L. stigma). The research was arranged in factorial experiment withcompletely randomized design, two factors and three replications.The first factor was type variant of M. anisopliae (V0= control, V1= variant UGM, V2= variant Karimun Jawa , V3= variant Semarang , V4 = variant Magelang), the second factor was type of pest (H1 = larva O. rhinoceros, H2 = larva L. stigma). The results showed that each variant of M. anisopliae had the same ability to control O. rhinoceros and L. stigma in both mortality, spore density, and LT50. O. rhinoceros has higher mortality and spore density than L. stigma, but LT50 both pests were the same. The interaction between O. rhinoceros and M. anisopliae gave the highest mortality, spore density, but the same LT50. Keywords : M. anisopliae, L. stigma, O. rhinoceros, mortality, spore density, LT50.